Functional role of ipsilateral motor areas in multiple sclerosis. Issue 5 (27th October 2010) - Zeller, Daniel; Dang, Su-Yin; Stefan, Katja; Biller, Armin; Bartsch, Andreas; Saur, Dorothee; Bendszus, Martin; Rieckmann, Peter; Toyka, Klaus V; Classen, Joseph
Abstract : Background: In patients with multiple sclerosis (MS), motor tasks are associated with increased activation of ipsilateral motor cortical areas. The authors examined the role of two ipsilateral motor areas during performance of a simple motor task in MS patients in relation to their motor impairment and CNS injury. Methods: Single pulses of transcranial magnetic stimulation (TMS) were used to interfere transiently with neuronal processing in the contralateral (M1CONTRA ) or ipsilateral (M1IPSI ) primary motor cortex or ipsilateral dorsal premotor cortex (PMdIPSI ) during a simple reaction time (RT) task in 26 right-handed patients with moderately severe stable MS and matched healthy controls. Subjects responded to an auditorily presented Go signal as quickly as possible by performing isometric right-thumb abductions. TMS was applied 100 ms after the Go signal. Motor impairment was evaluated by hand function tests. CNS injury was assessed by magnetic resonance spectroscopy (normalised N-acetyl-aspartate spectra, NAA/Cr), by the total cerebral T2-weighted MRI hyperintense lesion load, and by corticomuscular latency (CML) to the abductor pollicis brevis muscle. Results: TMS applied to M1CONTRA slowed RT in patients and controls. In contrast, stimulation of M1IPSI or PMdIPSI increased RT only in MS patients. In patients, the relative RT changes following TMS over M1IPSI or PMdIPSI did not correlate with any of the motor function tests or with NAA/Cr or total cerebral lesion load. However, RT changes following TMS over M1IPSI correlated inversely with CML. Conclusions: Recruitment of ipsilateral motor areas may be a functionally relevant, yet limited adaptive response to chronic brain injury in MS patients.